(untitled) (Journal of the College of Basic Education, 2024)
stem from a purely emotional desire And the actions of the Prophet Muhammad (PBUH), and from here the discussion is about the importance of the subject of jurisprudence (the verses of rulings in Surat Al-Nisa in the interpretation of Diaa Al-Furqan by Al-Sayyid Al-Naqwi) (may God have mercy on him) Because he was the owner of a jurisprudential theory, deriving his jurisprudential opinions from the Holy Qur’an, the Prophet’s Sunnah, and the narrations of the Ahl al-Bayt (peace be upon them), and the interpretation of the verses of rulings went through stages since the revelation began to descend to this day, so the first reference was the Messenger Muhammad (PBUH) Where he was explaining the meaning of the verse, interpreting it, and clarifying its ruling, Muslims took the path on the broad lines that were drawn by the greatest Messenger, writing the meaning of verse by verse, or clarifying it with the words of what came down to his heart of revelation, through his glorious Sunnah, and as jurisprudence arose and expanded its scope, and that is for the need of Muslims To fatwa and understand the legal provisions After that, it became a focus for the attention of scholars and jurists, as they devoted the greatest amount of their efforts to it, and they exerted most of their effort in order to know it and achieve it, so they explained the sub-rulings received from the Holy Book and the honorable Sunnah, and this nation gave birth to scholars who excelled in various types of science, especially Sharia Because of the importance of this book, I wanted to clarify the topics of the verses of rulings in its interpretation, including (hudud and felonies in Surat al-Nisa).